Greenwashing and Financial Performance of Publicly Listed Manufacturing Companies in Makassar - Istianah Hadaming; Wa Ode Rayyani (LPPM STIE Krakatau, 2026)
Purpose: This study aims to empirically analyze the impact of greenwashing practices on the financial performance (profitability/return on assets (ROA)) of manufacturing companies operating in Makassar. Methodology: This quantitative study employs secondary data obtained from publicly listed manufacturing companies (Tbk) operating in Makassar from 2021 to 2025. Data analysis was conducted using simple linear regression and content analysis to measure the level of greenwashing practices. Results: The statistical test results indicate that greenwashing practices have a negative but statistically insignificant effect on profitability (ROA). Conclusions: Symbolic environmental practices may reduce profitability owing to operational inefficiencies; however, the regional market remains highly pragmatic, where traditional financial metrics continue to dominate the determination of ROA-based valuation. Limitations: This study is limited to a specific geographical focus on the industrial area of Makassar and uses ROA as a proxy for financial performance. Contribution: This study provides empirical evidenceregarding ESG dynamics and greenwashing practices at the regional operational level, bridging the gap between corporate narratives developed at the headquarters level and their local implementation.